Pemetaan Potensi Bahaya Gempa Bumi di Provinsi Papua Barat Menggunakan Metode Percepatan Tanah Maksimum dan Point Source Analysis - Arif Faisol (Jurnal Natural, 2020)
Earthquakes are one of the main hazards in West Papua. Based on information from the National Disaster Management Authority (BNPB), the frequency of the destroyed earthquakes in West Papua is more than 9 times from 2002 until 2015. Peak Ground Acceleration (PGA) is one factor that caused destroy on earthquakes. This parameter has been used in this research to estimate the level of earthquakes hazard in West Papua at any period that combined with Point Source analysis and Gumbel distributions method. Seismic data recording of 1970 – 2017 that obtained from Meteorological, Climatological, and Geophysical Agency (BMKG) and United States Geological Survey (USGS) used in this research. The research shows that the level of earthquakes in West Papua is lower to the middle because the PGA value is < 0,70 g at any period. Generally, the level of earthquakes hazards in the north area more higher than in other areas because of some of the fault in the north area.